A functional collagen adhesin gene, acm, in clinical isolates of Enterococcus faecium correlates with the recent success of this emerging nosocomial pathogen - Nallapareddy, Sreedhar R; Singh, Kavindra V; Okhuysen, Pablo C; Murray, Barbara E (Infection and immunity, 2008)
Enterococcus faecium recently evolved from a generally avirulent commensal into a multidrug-resistant health care-associated pathogen causing difficult-to-treat infections, but little is known about the factors responsible for this change. We previously showed that some E. faecium strains express a cell wall-anchored collagen adhesin, Acm. Here we analyzed 90 E. faecium isolates (99% acm(+)) and found that the Acm protein was detected predominantly in clinically derived isolates, while the acm gene was present as a transposon-interrupted pseudogene in 12 of 47 isolates of nonclinical origin. A highly significant association between clinical (versus fecal or food) origin and collagen adherence (P <or= 0.0003) was also demonstrated, and levels of adherence were highly correlated (r = 0.879) with the amount of cell surface Acm detected by whole-cell enzyme-linked immunosorbent assay and flow cytometry. Thirty-seven of 41 sera from patients with E. faecium infections showed reactivity with recombinant Acm, while only 4 of 30 community and hospitalized patient control group sera reacted (P <or= 0.0003); importantly, antibodies to Acm were present in all 14 E. faecium endocarditis patient sera. Although pulsed-field gel electrophoresis indicated that multiple strains expressed collagen adherence, multilocus sequence typing demonstrated that the majority of collagen-adhering isolates, as well as 16 of 17 endocarditis isolates, are part of the hospital-associated E. faecium genogroup referred to as clonal complex 17 (CC17), which has emerged globally. Taken together, our findings support the hypothesis that Acm has contributed to the emergence of E. faecium and CC17 in nosocomial infections.